Performance of Disk Mill Type Mechanical Grinder for Size Reducing Process of Robusta Roasted Beans - Sri Mulato; Sukrisno widyotomo; Hadi Karia Purwadaria (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2007)
One of improtant steps in secondary coffee processing that influence on final product quality such as consistency and uniformity is milling process. Usually, Indonesian smallholder used "lumpang" for milling coffee roasted beans to coffee powder product which caused the final product not uniformed and consistent, and low productivity. Milling process of coffee roasted beans can be done by disk mill type mechanical grinder which is used by smallholder for milling several cereals. Indonesian Coffee and Cocoa Research Institute have developed disk mill type grinding machine for milling coffee roasted beans. Objective of this research is to find performance of disk mill type grinding machine for size reducing process of Robusta roasted beans from several size dried beans and roasting level treatments. Robusta dried beans which are taken from dry processing method have 13—14% moisture content (wet basis), 680—685 kg/m3 density, and classified in 3 sizes level. The result showed that the disk mill type of grinding machine could be used for milling Robusta roasted beans. Machine hascapacity 31—54 kg/h on 5,310—5,610 rpm axle rotation and depend on roasting level. Other technical parameters were 91—98% process efficientcy, 19—31 ml/ kg fuel consumption, 0.3—1% slips, 50—55% particles had diameter less than 230 mesh and 38—44% particles had diameter bigger than 100 mesh, 32—38% lightness was increased, 0.6—12.6% density was decreased, and solubility of coffee powder between 28—30%. Cost milling process per kilogram of Robusta roasted beans which light roast on capacity 30 kg/hour was Rp362.9. Key words : Coffee roasted, Robusta, disk mill, mechanical grinder, size reduction.